Maturity-related developmental inequalities in age-group swimming: The testing of 'Mat-CAPs' for their removal. Issue 4 (April 2021) - Abbott, Shaun; Hogan, Clorinda; Castiglioni, Marcela Torres; Yamauchi, Goshi; Mitchell, Lachlan J.G.; Salter, James; Romann, Michael; Cobley, Stephen
Abstract: Objectives: To (1) examine the association between maturity timing and performance-based selection levels in ( N  = 708) Australian male 100-m Freestyle swimmers (12–17 years); (2) identify the relationship between maturation status and 100-m Freestyle performance; and (3) determine whether Maturation-based Corrective Adjustment Procedures (Mat-CAPs) could remove maturation-related differences in swimming performance. Methods: In Part 1, maturity timing category distributions ('Early', 'Early Normative', 'Late Normative' and 'Late') for 'All', 'Top 50%' and '25%' of raw swimming times were examined within and across age-groups. In Part 2, multiple regression analyses quantified the relationship between maturity offset (YPHV) and swimming performance. In Part 3, sample-based maturity timing category distributions were examined based on raw and correctively adjusted swim times for 12–17 year old age-groups. Results: Based on raw swim times, a high prevalence of 'Early-maturing' swimmers, with large effect sizes was identified (e.g., 14 years 'All' — χ 2 (3, 151 = 111.98, p < 0.001; 'Early' v 'Late' OR = 82.0 95%CI = 4.77, 1409.9); while a complete absence of 'Late-maturers' was apparent in the sample ( N  = 708). When maturity categories were re-defined based on sample mean ± standard deviation, and when using the expected curvilinear trendline identified in Part 2, Mat-CAPs mitigated maturity timing biases across all age-groups and selection levels, and removed the Freestyle performance advantage afforded by advanced maturity timing and status. Conclusions: Removing the influence of maturation-related developmental differences could help improve youth swimmer participation experiences and improve the accuracy of identifying genuinely skilled age-group swimmers.